2017
DOI: 10.31436/ijpcc.v3i1.43
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Brainwaves While Listening To Quranic Recitation Compared With Listening To Music Based on EEG Signals

Abstract: the electroencephalogram (EEG) is an acquiring of the electrical fluctuationsthat occur in the brain, generated simply by positioning electrodes over the scalp withamplification of the electrical potential produced. The actual EEG indicates three primarytypes of wave, named alpha, beta and delta, which are distinct based on their rate ofproduction. Data has been collected from twenty five subjects using BrainMarker EEGhardware and software. Brainwaves were measured, focusing on the Alpha and Betabands to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The comparison of EEG changes during the shamanic state of consciousness and other spiritual or religious practices remains less clear. Previous studies have detailed increased alpha power (Abdullah and Omar, 2011 ; Al-Galal and Alshaikhli, 2017 ) and changes in relative alpha and theta power (Vaghefi et al, 2015 ) while listening to the recitation of the Quran, as well as increased approximate and sample entropy (Vaghefi et al, 2019 ). Additionally, increased absolute alpha power has been noted during catholic prayer (Barcelona et al, 2020 ), as well as increased relative alpha power during Muslim prayer (Doufesh et al, 2012 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of EEG changes during the shamanic state of consciousness and other spiritual or religious practices remains less clear. Previous studies have detailed increased alpha power (Abdullah and Omar, 2011 ; Al-Galal and Alshaikhli, 2017 ) and changes in relative alpha and theta power (Vaghefi et al, 2015 ) while listening to the recitation of the Quran, as well as increased approximate and sample entropy (Vaghefi et al, 2019 ). Additionally, increased absolute alpha power has been noted during catholic prayer (Barcelona et al, 2020 ), as well as increased relative alpha power during Muslim prayer (Doufesh et al, 2012 , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there were several studies that found holy Quran recitation produces alpha waves that indicated someone is relaxed. Alpha waves on participants who listened to the holy Quran were higher than participants who listened to relaxation music (Al-Galal & Alshaikhli, 2017). Neurotransmitters produced by auditory nerve pathways stimulate the primary auditory nerves and limbic cortex (Hall, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Jadi untuk artikel ini tidak ada perbedaan hasil antara mendengarkan Al-Quran dan music rileksasi. 13 Quran is Allah's words that are ultimately given to us human to benefit of. Although, Muslims are strongly believed that listening to Quran or reading it brings them to comfort, pleasure and confidence.…”
Section: Metodementioning
confidence: 99%